PERANCANGAN SISTEM INFORMASI GEOGRAFIS (SIG) PARIWISATA DI PROVINSI LAMPUNG - Yulmaini S.Kom., M.Cs; Ardi Dwi Saputra (IIB Darmajaya, 2012)
Lampung province is a southern province on the island of Sumatra, which have various tourism object such as both types, shapes, that viguries the unique of traditionality of the area. The goverment of Lampung province have made such kind of promotion to promote this tourism object through mass media: newspapers, brochures, posters and pamphlets. However this kind of methods have not been formed the touris, its self to the local and and foreign tourists. The method used in this reserach is Waterfall method (Waterfall Cycle). While the designing map in the system by using Google Maps API and software used in building this application is PHP ( Hypertext Pear Prepocessor ), JavaScript, jQuery as a programming language, XAMPP as the database server, Adobe Dreamweaver CS 3 as a support. Geographic information systems in Lampung tourism is a system that provides area, information to the public related the exicting tourism object in Lampung province. The information presented on the information of tourism object, travel maps , activities, tour and travel agents, hotels, restaurants, souvenir shops, and art galleries.Key Words : Lampung Tourism, Gheographic Information System.